Educable learning-oriented multilevel shared autonomy for inclusive mobility and healthcare - Vanderhaegen Frédéric; Ascone Corentin (ITM Web of Conferences)
This paper proposes a new paradigm based on educable learning for multilevel shared autonomy between humans and machines on future inclusive mobility or healthcare. Multilevel shared autonomy is presented from the perspective of three groups of process: a group of interactive supports, a group of roles of humans and machine in the course of shared autonomy and a group of sources or targets for inclusive mobility or healthcare. Two literature reviews present advances of the first two groups. Educable learning oriented multilevel shared autonomy is then proposed to recover limits of current approaches and to update online or offline learning or education supports. A case study illustrates the feasibility of such educable learning process.